2011
DOI: 10.1038/ismej.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metagenomics of microbial traits within oceanic viral communities

Abstract: Viral genomes often contain genes recently acquired from microbes. In some cases (for example, psbA) the proteins encoded by these genes have been shown to be important for viral replication. In this study, using a unique search strategy on the Global Ocean Survey (GOS) metagenomes in combination with marine virome and microbiome pyrosequencing-based datasets, we characterize previously undetected microbial metabolic capabilities concealed within the genomes of uncultured marine viral communities. A total of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(145 citation statements)
references
References 55 publications
2
140
1
2
Order By: Relevance
“…Given that sufA is homologous to iscA (Ollagnier-de-Choudens et al, 2004), it cannot be confirmed whether one or both genes are present; however, both function as scaffold proteins in Fe-S cluster assembly indicating that this is likely important in viruses. Another such biogenesis gene (sufE) was also detected and has been previously documented in viromes (Sharon et al, 2011), but occurred in only 12 of the 16 POV photic zone viromes. In addition, three PCE genes suggest that Pacific Ocean viruses also augment Fe-S protein folding (ATP-dependent molecular chaperone, (clpX)) and degradation of Fe-S cluster proteins (serine protease (clpP) and DNA-binding ATPdependent protease La (lon) (Rouault and Tong, 2005)), although their functions may be generalizable to other proteins.…”
Section: Co-localized With Viral Genes On Contigs (Includes Genes Idementioning
confidence: 62%
See 3 more Smart Citations
“…Given that sufA is homologous to iscA (Ollagnier-de-Choudens et al, 2004), it cannot be confirmed whether one or both genes are present; however, both function as scaffold proteins in Fe-S cluster assembly indicating that this is likely important in viruses. Another such biogenesis gene (sufE) was also detected and has been previously documented in viromes (Sharon et al, 2011), but occurred in only 12 of the 16 POV photic zone viromes. In addition, three PCE genes suggest that Pacific Ocean viruses also augment Fe-S protein folding (ATP-dependent molecular chaperone, (clpX)) and degradation of Fe-S cluster proteins (serine protease (clpP) and DNA-binding ATPdependent protease La (lon) (Rouault and Tong, 2005)), although their functions may be generalizable to other proteins.…”
Section: Co-localized With Viral Genes On Contigs (Includes Genes Idementioning
confidence: 62%
“…Seven of these were observed previously in viral genomes and metagenomes including thyA, def (PDF), dnaB, dnaG, xerC, ligD and dam (Scherzinger et al, 1977;Yonesaki, 1994;Subramanya et al, 1996;Huber and Waldor, 2002;Pitcher et al, 2006;Sullivan et al, 2010;Sharon et al, 2011). The two that are newly described for viruses include genes encoding an endonuclease (uvdE) and a phosphate transport protein (phoU).…”
Section: Co-localized With Viral Genes On Contigs (Includes Genes Idementioning
confidence: 91%
See 2 more Smart Citations
“…similar to a domain from the "metabolism" category) were then selected for further study because of their central role in sulfur (dsrC and soxYZ) or nitrogen (P-II, amoC) cycle, and the fact that these had never been detected in a surface ocean viral genome so far (dsrC/tusE-like genes have been detected in deep water viruses 14,29 ). To evaluate if an AMG was "known", a list of PFAM domain detected in NCBI RefSeqVirus and Environmental Phages was computed based on a similar hmmsearch comparison (threshold of 40 on bit score and 0.001 on e-value), and augmented by manual annotation of AMGs from 24,82 . The complete list of PFAM domains detected in GOV viral contigs is available as Supplementary Table 5.…”
Section: Identification and Annotation Of Putative Amgs Detection Of mentioning
confidence: 99%